Managing difficult interactions expert solutions to everyday challenges. - Harvard Business School. Press (Boston, Mass. : Harvard Business Press, 2008)
In the business world, confrontations are inevitable-whether they're with your employees, peers, bosses, or even suppliers and customers. Ignored or handled badly, confrontations can damage workplace relationships and ruin careers. (Barnes & Noble)
Includes bibliographical references (p. 77-84).
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on print version record.
Keywords: Conflict management; Interpersonal confrontation; Interpersonal conflict; Interpersonal communication; Interpersonal relations; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books